2020
DOI: 10.3934/publichealth.2020039
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the access to health services among waste collectors in Hanoi, Vietnam: A qualitative study

Abstract: Background Waste collection is a common practice in Vietnam. In general, the working and living conditions of waste collectors are poor. Thus, they might be exposed to occupational and environmental risk factors, which affect their health or could further exacerbate their health vulnerabilities. Moreover, they have difficulties to access to health services. Objective The aim of this study was to understand factors affecting the access to health services among waste coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Is the analysis method clearly explained and appropriate for the study? (9)(10)(11). The majority (n = 14) of the studies were conducted in developing countries.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Is the analysis method clearly explained and appropriate for the study? (9)(10)(11). The majority (n = 14) of the studies were conducted in developing countries.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Eight studies (8)(9)(10)(11)(12)(13)24) discovered affordability as one of the significant barriers to healthcare for young informal workers across diverse industries. Five studies (7-11) identified the cost of seeking formal healthcare as one of the problems young informal workers are unable to seek the healthcare they need.…”
Section: Affordability Of Healthcarementioning
confidence: 99%
See 2 more Smart Citations
“…Pekerjaan mengumpulkan sampah adalah pekerjaan yang berpotensi menimbulkan beberapa penyakit (Cruvinel, 2019), di antaranya adalah penyakit dermatitis (Nam et al, 2020). Prevalensi kejadian dermatitis dapat dipengaruhi frekuensi kontak yang sering dan masa kerja yang lama (Pradananingrum et al, 2018).…”
Section: Pendahuluanunclassified